ENT 530 Social Media Portfolio : Young Living Essential Oils By Laily / Nor Laili Ibrahim - Ibrahim, Nor Laili (2021)
Young Living is a United States-based brand that uses the Seed to Seal technique to produce 100% natural essential oils. From the seed selection through the bottling of the essential oils, every step is carefully monitored and researched to ensure that no chemicals are contained. Young Living Essential Oils are also known as aromatherapy oils for skin, hair, and beauty. There are two types of membership programs which the first is Standard Membership that can only be purchased at the member price and does not need to be consistent. To get this membership, I need to buy Basic Starter Kit or Premium Basic Starter Kit. Second, Essential Reward Membership does not require membership fees and has many benefits. It just needs to buy essential oils only and there are 3 types of options to choose from. First, 100pv (point value) Membership; is equivalent to RM 560, second is Membership 150pv is equivalent to RM 760pv and the third is Membership 300pv and above is equivalent to RM 1500. Thus, Young Living Essential Oil by Laily was created in a way that required me to be a member of Young Living that under the guidance of Encik Muhammad Faharudin. I choose the Standard Membership program as the first step for me and since this is my first time venturing into the business, Young Living Essential Oil by Laily will concentrate solely only on essential oil products sales.